2019
DOI: 10.1002/anie.201902009
|View full text |Cite
|
Sign up to set email alerts
|

A Stable, Non‐Corrosive Perfluorinated Pinacolatoborate Mg Electrolyte for Rechargeable Mg Batteries

Abstract: Mg batteries are a promising energy storage system because of physicochemical merits of Mg metal as an anode material. However, the lack of electrochemically and chemically stable magnesium electrolytes impedes the development of Mg batteries. In this study, a newly designed chloride-free magnesium fluorinated pinacolatoborate, Mg[B((CF3)4C2O2)2]2 (abbreviated as Mg-FPB), was synthesized by convenient methods from commercially available reagents and fully characterized. The Mg-FPB electrolyte delivered outstan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 23 publications
5
113
0
2
Order By: Relevance
“…Tetrakis(hexafluoroisopropyloxy)borate anion (denoted as B(hfip) 4 − ) based Mg electrolytes have been reported almost simultaneously by our group and Zhao's group, which exhibits superior electrochemical performance, especially in Mg‐S battery system 4e,h,11. However, in this contribution, we have observed that the Mg/Cu asymmetric cell (with Mg[B(hfip) 4 ] 2 based electrolyte, 0.5 m Mg[B(hfip) 4 ] 2 dissolved in dimethoxyethane (DME), abbreviated as MBhfip/DME) cannot sustain the stability in the long cycle charge–discharge process, as shown in Figure S1 (Supporting Information).…”
Section: Figurementioning
confidence: 85%
See 2 more Smart Citations
“…Tetrakis(hexafluoroisopropyloxy)borate anion (denoted as B(hfip) 4 − ) based Mg electrolytes have been reported almost simultaneously by our group and Zhao's group, which exhibits superior electrochemical performance, especially in Mg‐S battery system 4e,h,11. However, in this contribution, we have observed that the Mg/Cu asymmetric cell (with Mg[B(hfip) 4 ] 2 based electrolyte, 0.5 m Mg[B(hfip) 4 ] 2 dissolved in dimethoxyethane (DME), abbreviated as MBhfip/DME) cannot sustain the stability in the long cycle charge–discharge process, as shown in Figure S1 (Supporting Information).…”
Section: Figurementioning
confidence: 85%
“…However, this system is generally known to possess unsatisfactory energy density owing to the low operating voltage (≈1.1 V) and the low specific capacity (80 mAh g −1 ) of Mo 6 S 8 cathode. Since then, tremendous endeavors have been devoted to improving the energy density of rechargeable Mg metal batteries, aimed at exploiting the high‐voltage Mg cathode and developing the high‐performance Mg electrolytes …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Simple Mg salts including Mg(TFSI) 2 and Mg (PF 6 ) 2 were confirmed as not working for reversible Mg deposition due to the instability of anions with Mg metal. [46,48] Magnesium carborane, [49][50][51] Magnesium hexafluoroisopropylaluminate, [52] Magnesium hexafluoroisopropylborate, [53][54][55] and Magnesium perfluorinated pinacolatoborate [56] salts were reported as rare examples of Cl-free non-corrosive electrolytes for reversible Mg deposition.…”
Section: Introductionmentioning
confidence: 99%
“…So sind für Lithiumionenbatterien geeignete Boratanionen nicht notwendigerweise auch für andere Batterieklassen die beste Wahl. Erst kürzlich konnte beispielsweise Mg[B{O 2 C 2 (CF 3 ) 4 } 2 ] 2 als vielversprechendes, chlorfreies Elektrolyt in Magnesiumbatterien ausgemacht werden ( FPB , Abbildung ) …”
Section: Boratanionen Und Anionische Borcluster Als Bausteine Für Eneunclassified